2019
DOI: 10.1037/men0000207
|View full text |Cite
|
Sign up to set email alerts
|

Understanding disordered eating in Black adolescents: Effects of gender identity, racial identity, and perceived puberty.

Abstract: Gender identity has been identified as a risk factor for disordered eating behaviors (DEB) in adolescents. However, extant studies have been slow to consider the combined influence of multiple social identities. This study examined whether social identities (gender and race) interact with perceived pubertal timing relative to peers, to predict DEB in Black adolescents and whether these relations were moderated by biological sex. Data are drawn from Black adolescents (N = 328; 42% male) who participated in Wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…Ge et al (2006) demonstrated that early pubertal timing and more advanced pubertal development predicted the highest levels of anxiety and depressive symptoms among African American boys. Late pubertal timing also appears to be problematic for the mental health and self-concepts of African American boys (Blazek & Carter, 2019;Carter, 2015;Carter, Caldwell, Matusko, & Jackson, 2015). Carter (2015) demonstrated that African American boys who perceived their development as late relative to their same-sex, same-age peers reported higher levels of anxiety symptoms relative to early and ontime African American boys.…”
Section: Pubertal Development Self-concept and Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge et al (2006) demonstrated that early pubertal timing and more advanced pubertal development predicted the highest levels of anxiety and depressive symptoms among African American boys. Late pubertal timing also appears to be problematic for the mental health and self-concepts of African American boys (Blazek & Carter, 2019;Carter, 2015;Carter, Caldwell, Matusko, & Jackson, 2015). Carter (2015) demonstrated that African American boys who perceived their development as late relative to their same-sex, same-age peers reported higher levels of anxiety symptoms relative to early and ontime African American boys.…”
Section: Pubertal Development Self-concept and Depressive Symptomsmentioning
confidence: 99%
“…Yet early pubertal effects are substantially less well understood among boys than girls (see Deardorff, Hoyt, Carter, & Shirtcliff, 2019). Early development may be particularly detrimental because girls tend to develop earlier than boys and their maturation moves them further away from the thin feminine ideal, whereas boys tend to develop later than girls and their pubertal development causes increased muscle development bringing them closer to the muscular masculine ideal (Blazek & Carter, 2019). If early puberty is problematic for boys, more research is needed to better understand the underlying mechanisms linking early puberty to negative outcomes among this population.…”
mentioning
confidence: 99%
“…There is also a lack of empirical research examining the impact of race- or ethnic-related variables that shape the social experiences of early-maturing boys (Ge & Natsuaki, 2009). Although early pubertal development may place Black American boys at increased risk of harm (see Goff et al, 2014; Schultz, 2015), recent empirical research indicated that pubertal development is nuanced and complex when disentangling race and ethnicity among Black American boys (see Blazek & Carter, 2019; Carter, Leath, et al, 2017; Carter, Seaton, et al, 2017; Carter et al, 2020; Seaton & Carter, 2020). The present study examined the ethnic–racial composition of neighborhoods as a moderator in the relation between pubertal timing and depressive symptoms among a nationally representative sample of African American and Caribbean Black boys.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…According to Phinney and Ong, (2007), the development of ethnic identity is an active process that changes with time and context, and its previously mentioned dimensions provide a framework for comparing ethnic identity with other types of group identity (Phinney & Ong, 2007). Other researchers have adapted this definition to apply to other aspects of identity, including Muslim American identity (Lowe et al, 2019), racial identity (Blazek & Carter, 2019), and lesbian, gay, and bisexual group identity (Sarno & Mohr, 2016). In the current study, the research team consulted with the leadership of ( masked for blind review ) the Muslim Student Association (MSA) and decided to examine participants’ Muslim identity separate from their American identity, as most members considered these distinctive identities.…”
Section: Literature Reviewmentioning
confidence: 99%